An Analysis of Quality Management (QM) of School Management in School Accreditation Grade A - Shopia, Khilda; Sabila, Dara (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT Education quality is important for those who are involved in that school either directly or indirectly such as principle, headmaster, teacher, staff administration, students, parents and etc. A case study was used to get the overview about the quality management in school's management at SMA Negeri 1 Subang based on the school's accreditation grade A. Quality Management (QM) was employed as an approach in analyzing and characterizing the school's quality management. The purpose of study was to identify the criteria, standards and indicators in management of school, to get the overview how to get the good quality in education based on the school's accreditation A. Quality Management will be focused in analyzing management of the school. The result illustrated that QM can be used as an approach in analyzing the quality of education. There are seven indicators that should be achieved in quality management; curriculum, achievement, learning and teaching, students' support, school's ethos, resources and management, leadership and quality assurance. Quality of education organized by the member of school and it should contribute each other between principle, headmaster, staff administration, teacher, students and parents. Principles and criteria used based on Quality Management that there should be the process of plan, do, check, and act continuously. Thus, quality management in education should be designed cooperatively in the members of the school and as an evaluation it should be monitored continuously. Keyword: Quality Management, School's Management, Language Education, English as a Foreign Language